Overview of Albanian Literary Criticism 1912-1944 - Gugu, Edlira (Richtmann Publishing, 2012)
The purpose of this paper is to explain the development of Albanian literary criticism in the early twentieth century. This studyis intended to create a panorama of Albanian literary criticism, taking into account a number of key components that enabled the birth ofAlbanian literary critical thought, its development and maturation. This paper also intends to approach the study of Albanian literarycriticism diachronically and synchronically. These approaches create an opportunity to interpret how literary criticism developed in theperiod 1912-1944. The reason for using these methods is to give a complete overview of the steps of Albanian literary criticism. Thisstudy carefully constructs a socio-cultural context of the period and shows how the social-cultural context creates the necessaryconditions for the emergence of literary criticism in Albania. This study also shows the most well known representatives and types ofliterary criticism. Special attention is paid to problems that accompanied the origins of Albanian literary criticism. These problems areclassified according to their literary genres developed in the period 1912 -1944.